1996
DOI: 10.1046/j.1526-4610.1996.3601029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sumatriptan on Brain Monoamines in Rats

Abstract: Clinical data suggests that sumatriptan is effective in the acute treatment of migraine. The vascular effects of the drug have been invoked to explain this antimigraine efficacy. However, the effect of sumatriptan on brain monoamines has not previously been investigated. In order to study these hypothetical effects, we administered the drug to 24 male rats, subcutaneously, at three doses (0.3, 0.6, and 0.9 mg/kg of body weight), and 30 minutes later, all animals were decapitated. Dopamine, serotonin, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As observed in different experimental conditions, triptan-sensitive 5HT 1B/1D receptors are predominantly terminal autoreceptors inhibiting 5HT release and/or synthesis and decreasing brain 5HT level [14, 15]. Acute, systemic application of sumatriptan and zolmitriptan in rats was found to decrease the 5HT synthesis in many brain regions, including the dorsal raphe nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in different experimental conditions, triptan-sensitive 5HT 1B/1D receptors are predominantly terminal autoreceptors inhibiting 5HT release and/or synthesis and decreasing brain 5HT level [14, 15]. Acute, systemic application of sumatriptan and zolmitriptan in rats was found to decrease the 5HT synthesis in many brain regions, including the dorsal raphe nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Again, rats were injected with saline, agonist, or antagonist 4 h before killing. The doses of the serotonergic drugs used were determined based on the appropriate literature reports, specifically: 8-OH-DPAT, Owens et al (1990); sumatriptan, Mitsikostas et al (1996); GR 127935, Skingle et al (1996); DOI, Vaidya et al (1997); ketanserin, Semont et al (2000); RO 600175, Dekeyne et al (1999); SB 206553, Kennett et al (1996).…”
Section: Acute Treatments and Cell Proliferationmentioning
confidence: 99%
“…In that study, rats given high subcutaneous doses of sumatriptan (0n6 mg\kg) demonstrated reduced hypothalamic concentrations of 5-HT and increased turnover of both dopamine and 5-HT. Although this dose is very high compared with that used in the treatment of migraine (approximately 0n08 mg\kg), the plasma concentration achieved (70 ng\ml) was similar to that seen in humans after a single 6 mg subcutaneous injection (72n4 ng\ml) [30,31]. Whether such an effect would be seen in humans is debatable, and impractical to confirm given our current inability to measure brain levels of neurotransmitters without invasive procedures.…”
Section: Discussionmentioning
confidence: 82%
“…Sumatriptan has also been shown to have neurogenic blocking properties in animal models, reducing trigeminal ganglion activation in response to chemical stimulation [29]. It is possible, due to the central connections to the trigeminal nucleus caudalis in the medulla oblongata, that subcortical levels of monoamines may be affected, as has been shown in rats [30]. In that study, rats given high subcutaneous doses of sumatriptan (0n6 mg\kg) demonstrated reduced hypothalamic concentrations of 5-HT and increased turnover of both dopamine and 5-HT.…”
Section: Discussionmentioning
confidence: 96%